Fabrication of flexible polyurethane/phosphorus interpenetrating polymer network (IPN) foam for enhanced thermal stability, flame retardancy and mechanical properties. (July 2021) - Ma, Chao; Zhang, Kang; Zhou, Feng; Zheng, Yapeng; Zeng, Wenru; Wang, Bibo; Xing, Weiyi; Hu, Weizhao; Hu, Yuan
Highlights: A liquid flame retardant, phosphorus-containing triacrylate, was synthesized. Flexible polyurethane/phosphorus-containing polyacrylate IPN foams were prepared by simultaneous strategy. Flame retardancy, thermal stability and mechanical properties of IPN foams were improved concurrently. Abstract: Even though organophosphorus additives can improve flame retardancy and compress strength of flexible polyurethane foam (FPUF), but thermal stability and resilience are deteriorated. In this work, phosphorus-containing monoacrylate and triacrylate, (dimethoxyphosphoryl)methyl acrylate (DMPMA) and tris(acryloyloxymethyl)phosphine oxide (TAMPO), were synthesized. The liquid DMPMA and/or TAMPO were added into FPUF ingredients with radical initiator and polymerized in the heating process after foaming to form FPUF/polyacrylate composites. The neat and modified foams were controlled to have similar densities. Gel content of more than 96% was obtained for FPUF incorporated with TAMPO. And structure of interpenetrating polymer network (IPN) of FPUF3-5 loaded 20 wt% DMPMA and TAMPO of polyol (ratio of 3:1, 1:1 and 1:3 respectively) was further confirmed by their bicontinuous phase morphology with nanoscale domain uniformly distributed. All modified foams attain improved flame retardancy. Simultaneously increased thermal stability, compression force deflection (CFD) value and resilience were achieved by FPUF4-5. Especially, FPUF4 exhibits satisfied flame retardancy (limited oxygen index of 22.1%, pass of TB117-2000 vertical burning test, prolonged time to ignition, 49% decrement of peak heat release rate and 33% reduction of total heat release), elevated thermal stability and improved compressive (15% improvement of CFD) and resilient (5.2% raise of resilience) properties, concurrently. Therefore, DMPMA and TAMPO have great potential as liquid additive-type flame retardants for manufacturing flame retardant, supportive and comfort FPUF in seating and cushioning applications.